2010
DOI: 10.1007/s10508-010-9632-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to Suggest that Copulatory Vocalizations in Women Are Not a Reflexive Consequence of Orgasm

Abstract: The current studies were conducted in order to investigate the phenomenon of copulatory vocalizations and their relationship to orgasm in women. Data were collected from 71 sexually active heterosexual women (M age = 21.68 + .52) recruited from the local community through opportunity sampling. The studies revealed that orgasm was most frequently reported by women following self-manipulation of the clitoris, manipulation by the partner, oral sex delivered to the woman by a man, and least frequently during vagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 17 publications
5
21
0
2
Order By: Relevance
“…This is in agreement with the study of Brewer and Hendrie [12], who indicated that most CV in women do not accompany their own orgasm, but rather their partner's ejaculation. This is in agreement with the study of Brewer and Hendrie [12], who indicated that most CV in women do not accompany their own orgasm, but rather their partner's ejaculation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with the study of Brewer and Hendrie [12], who indicated that most CV in women do not accompany their own orgasm, but rather their partner's ejaculation. This is in agreement with the study of Brewer and Hendrie [12], who indicated that most CV in women do not accompany their own orgasm, but rather their partner's ejaculation.…”
Section: Discussionsupporting
confidence: 92%
“…Similar reasons were reported in the study of Brewer and Hendrie [12]. Similar reasons were reported in the study of Brewer and Hendrie [12].…”
Section: Discussionsupporting
confidence: 87%
“…According to the authors, the copulatory vocalizations can thus be one of the potential strategies used by the female to advertise receptivity to the high-ranking males, to confuse fatherhood and to provide future support from these socially important individuals. In the case of women, it was also recognized that at least one element of these responses was under conscious control, providing them with an opportunity to manipulate the male behavior, e.g., to accelerate partner's orgasm, when a woman was already weary (Brewer and Hendrie 2011).…”
Section: Female Mating Predispositionsmentioning
confidence: 99%
“…он сообщил, что вокализации использовались для ускорения наступления эякуляции у партнера. В статье, посвященной данной проблеме [36], указанные авторы сообщают, что проведенные ими исследования свидетельствовали о более частом возникновении оргазма у женщин при само-стимуляции клитора, манипуляции со стороны партнера, кунилингусе и гораздо более редком его возникновении при влагалищном проникновении.…”
Section: рекомендации по имитации оргазма женщинамиunclassified